Potential of Fruit Peel Waste in Growing Cyanobacteria Anabaena cylindrica - Tan Yeong Hwang; Ho An Qi; Chai Mee Kin; Wong Ling Shing; Djearamane Sinouvassane; Thirunavukkarasu Chinnasamy (International Journal of Technology, 2021)
Fruit peels are usually disposed of or treated as fertilizer. The peel, however, contains rich nutrients that can be used as a medium for growing microbes. Conventional culture medium is widely used for growing microbes, but the cost is very high and it is not suitable to produce cyanobacterium-based biofuel, biomass, and in other applications. Therefore, this study explores the potential for using fruit peels as a culture medium for Anabaena cylindrica. The fruit peels were dried, homogenized, and filtered to make different concentrations of fruit peel media (5%, 10% and 20%). For comparison, BG-11 medium acted as a positive control whereas deionized water serves as a negative control in this experiment. Growth of A. cylindrica in different types of media was analyzed after cell counting using a hemacytometer and biomass measuring.  The cyanobacterial growth rate and biomass production were recorded in different types of fruit peel media with different concentrations. A. cylindrica have greater biomass yield when growing in 20% papaya peel medium and a higher growth rate when growing in 10% pineapple peel media compared to that growing in the BG-11 medium. In other words, the fruit peel media have more potential in growing cyanobacteria than conventional medium.